Fabrication and electrical characteristics of flash-sintered SiO2-doped ZnO-Bi2O3-MnO2 varistors - Pai Peng; Yujun Deng; Jingpeng Niu; Liyi Shi; Yunzhu Mei; Sanming Du; Juan Liu; Dong Xu (Journal of Advanced Ceramics, 2020)
Abstract The dense ZnO-Bi2O3-MnO2-xSiO2 (ZBMS) varistors for x = 0, 1, 2, 3 wt% were fabricated by flash sintering method under the low temperature of 850 °C within 2 min. The sample temperature was estimated by a black body radiation model in the flash sintering process. The crystalline phase assemblage, density, microstructure, and electrical characteristics of the flash-sintered ZBMS varistors with different SiO2-doped content were investigated. According to the XRD analysis, many secondary phases were detected due to the SiO2 doping. Meanwhile, the average grain size decrease with increasing SiO2-doped content. The improved nonlinear characteristics were obtained in SiO2-doped samples, which can be attributed to the ion migration and oxygen absorption induced by the doped SiO2. The flash-sintered ZBMS varistor ceramics for x = 2 wt% exhibited excellent comprehensive electrical properties, with the nonlinear coefficient of 24.5, the threshold voltage and leakage current of 385 V·mm−1 and 11.8 µA, respectively.